TRADISI, AGAMA, DAIS MODERTOSASI DALAM FERKEMBANGAIN KEBUDAYAAN TIMOR - WindiyartI, Dara (Fakultas Ilmu Budaya Universitas Diponegoro, 2006)
Timor culture is one of the enchanting culture in Indonesia. The relationship between Protestant religion and the local culture has created a new culture. In the traditional society, the development of modern culture may lead to a sensitive situation in which new values confront the old existing values. Therefore, alertness and sensitivity are required to comply with the subjective view of society toward such development